'Do not dare speak of Scientology in France!' - Rigal-Cellard, Bernadette (Implicit religion, 2020)
In this article I contrast the ease with which I have always been able to study Scientology with the near impossibility to speak about my research in France unless it is to attack the Church, considered as the epitome of the dangerous tentacular cult. Any factual presentation of its origins and workings will be interpreted as a biased promotion of this dangerous ‘secte.’ I narrate a year-long attack by anti-cultists against my work and against CESNUR.